Post-colonial study of El Primer Sale El Conde Villaroso con Todos Consejeros Junta Real (A comedia). Marites J. Dava. - Dava, Marites J. (2007.)
The study was undetaken to identify the postcolonial aspects of the comedia. It generally aims to expose its post colonial aspect by identifying the different ideologies that flourished related to Muslim-Christian relations, describing the significance of the "comedia" text in empowering local culture and identifying that forms of resistance present in text. The study was the composition of comedia entitled El Primer Sale El Conde Villaroso con todos Consejeros Junta Real. This was written during 1979 in mixed Spanish and Hiligaynon languages. Finally, Christians and Muslims need to explore seriously models of governance that further a balance between individual and community rights. Such situations also challenge us to develop new forms of political involvement. This involvement necessitates an ability to liberate religion from narrow sectional interests, with the aim of engaging critically in issues of human rights and social and political justice and striving towards peaceful resolution of conflicts.
Thesis (Undergraduate, Bachelor of Arts in Literature) College of Arts and Sciences, University of the Philippines Visayas, Miag-ao, Iloilo.
Keywords: Comedia